2006
DOI: 10.1007/s00280-006-0299-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of weekly DN-101, a new formulation of calcitriol, in patients with cancer

Abstract: The MTD for weekly DN-101 was established as 45 mug. The DLTs observed were two episodes of rapidly reversible grade 2 hypercalcemia in two of the six patients treated at 60 microg weekly. Repeat doses of DN-101 at 45 microg weekly are well tolerated and this dose is suitable for studies of weekly DN-101 in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…DLT of grade 2 hypercalcemia occurred in two out of six patients and the MTD was established at 45 µg. At a weekly dose of 45 µg, the treatment was well tolerated and there was no sign of drug accumulation or induced metabolism [108]. As DN-101 does not add significantly to mitoxantrone and prednisone alone [109], further investigations of Beer and colleagues focused on calcitriol and docetaxel combination therapies.…”
Section: Clinical Studies Of Vitamin D Analogs and In Combination With mentioning
confidence: 98%
“…DLT of grade 2 hypercalcemia occurred in two out of six patients and the MTD was established at 45 µg. At a weekly dose of 45 µg, the treatment was well tolerated and there was no sign of drug accumulation or induced metabolism [108]. As DN-101 does not add significantly to mitoxantrone and prednisone alone [109], further investigations of Beer and colleagues focused on calcitriol and docetaxel combination therapies.…”
Section: Clinical Studies Of Vitamin D Analogs and In Combination With mentioning
confidence: 98%
“…With the new formulation, peak plasma concentrations >1,000 pg/ml have been observed in some patients. There may also be less interpatient variability in peak plasma concentrations with the new formulation, given that patients have to take fewer capsules than with the lower dose capsules [28].…”
Section: Discussionmentioning
confidence: 99%
“…A reformulation of ILX23-7553 might facilitate achieving higher plasma concentrations as up to 18 tablets per day of ILX23-7553 were required to be ingested at one time at the highest dose levels [27]. For example, a new formulation of calcitriol (DN-101) in which 15 μg are administered in a single capsule, as compared to the previous 0.5 μg per capsule formulation, was evaluated in a phase I study [28]. With the new formulation, peak plasma concentrations >1,000 pg/ml have been observed in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…6,30 Clinical trials demonstrated that calcitriol can be safely administered to achieve sufficient doses in patients as compared to the doses given in the in vitro model systems. [15][16][17]31 Therefore, we investigated whether calcitriol would enhance the antitumor activity of gemcitabine in a pancreatic adenocarcinoma model system Capan-1.…”
Section: Discussionmentioning
confidence: 99%